THE STUDY OF ORGANOPHOSPHATE (DIAZINON) TOXICITY TOWARD LIVER HISTOPATHOLOGY AND MALONDIALDEHYDE (MDA) SERUM LEVELS ON RATS (Rattus norvegicus) - Pratama, Dyah Ayu Oktavianie; Aulia, Zulfa; Aulanni'am, Aulanni'am; Permata, Fajar Shodiq (Faculty of Veterinary Medicine Universitas Brawijaya, 2019)
Diazinon is an insecticide that has a higher toxicity than other insecticides. Normally, insecticides are detoxified by liver, but this process produced free radicals which causes cell damage. Free radicals also increase lipid peroxidation which directly increase malondialdehyde levels. This research was aimed to determine the influence of diazinon toxicity to the liver histopathology and levels of malondialdehyde (MDA) in the serum of rats (Rattus norvegicus). The rats were divided into 4 groups which consist of negative control group and three experimental groups which were given diazinon 20 mg/kgBW (P1), 40 mg/ kgBW (P2), and 60 mg/ kgBW (P3). The rats were given diazinon for 8 weeks orally. The parameters used in this research was liver histopathology with hematoxilin eosin stain and Malondialdehyde levels with Thiobarbituric test. Liver histopathology was analyzed in descriptive qualitative and the level of MDA was analyzed quantitatively using ANOVA and Tukey's exact test with Î± = 0.05. The result of this research showed the influence of organophosphate (diazinon) on liver histolopathology was shown by inflammatory cells infiltration in hepatic parenchyma, sinusoidal congestion, and cytoplasmic vacuolation of the hepatocytes. Statistical analysis proved that the diazinon was able to increase the level of MDA serum significantly (p<0,05) up to 71% in experimental group P1 (dose 20 mg/kgBW), which the increase level of MDA serum depend on dose of diazinon. This research concluded that diazinon is one of the organophosphate pesticide that toxic based on liver histopathology and MDA serum levels.Â